High impact nutrition and dietetics journals’ use of publication procedures to increase research transparency - Dennis M. Gorman; Alva O. Ferdinand (Research Integrity and Peer Review, 2020)
Abstract Background The rigor and integrity of the published research in nutrition studies has come into serious question in recent years. Concerns focus on the use of flexible data analysis practices and selective reporting and the failure of peer review journals to identify and correct these practices. In response, it has been proposed that journals employ editorial procedures designed to improve the transparency of published research. Objective The present study examines the adoption of editorial procedures designed to improve the reporting of empirical studies in the field of nutrition and dietetics research. Design The instructions for authors of 43 journals included in Quartiles 1 and 2 of the Clarivate Analytics’ 2018 Journal Citation Report category Nutrition and Dietetics were reviewed. For journals that published original research, conflict of interest disclosure, recommendation of reporting guidelines, registration of clinical trials, registration of other types of studies, encouraging data sharing, and use of the Registered Reports were assessed. For journals that only published reviews, all of the procedures except clinical trial registration were assessed. Results Thirty-three journals published original research and 10 published only reviews. Conflict of interest disclosure was required by all 33 original research journals. Use of guidelines, trial registration and encouragement of data sharing were mentioned by 30, 27 and 25 journals, respectively. Registration of other studies was required by eight and none offered Registered Reports as a publication option at the time of the review. All 10 review journals required conflict of interest disclosure, four recommended data sharing and three the use of guidelines. None mentioned the other two procedures. Conclusions While nutrition journals have adopted a number of procedures designed to improve the reporting of research findings, their limited effects likely result from the mechanisms through which they influence analytic flexibility and selective reporting and the extent to which they are properly implemented and enforced by journals.